The Influence Of Bank Product Socialization And Electronic Payment System Quality On Intention To Use E-Money In Indonesia - Cynthia Jonathan; Rina Erlanda; Zainal Arifin Hidayat (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This research aims to provide empirical evidence that bank product socialization andelectronic payment system quality positively influence intention to use e-money. This research is important to be done for the sake of The Bank of Indonesia and all of Indonesian people because there are a lot of benefits would be acquired by a massive using of e-money. The population of this research is all of Indonesian people and the sample that taken for this research are 209 respondents from the college/ university students in Indonesia. The independent variables which are used in this research are bank product socialization andelectronic payment system quality. Meanwhile, the dependent variable which is used in this research is intention to use e-money. The survey result which showed that the using level of e-money is very low which only 26% from all of the respondents indicates that The Bank of Indonesia have to increase the effort of bank product socialization and control the quality of electronic payment system.